On government-subsidized training programs for older workers - Christine Singer; Ott-Siim Toomet (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
We analyze the impact of the GermanWeGebAU programs, which are government-subsidized training measures for employed workers over 45 years old. We apply a dynamic matching approach similar to Crépon et al. (2009) and exploit novel information contained in rich German registry data. We focus on the effects on survival probability in original employment and estimate the effects separately by gender, age, job status, and program duration. We find that WeGebAU training improves the probability of remaining in paid employment by 1.0 to 2.5 percentage points in the two-year period following treatment. The effect is more pronounced for part-time workers and longer-duration program participants. Our analysis suggests that postponed labor market withdrawal is the main driver of the positive effects and that there is selection into treatment at the firm level. – – Wir untersuchen die Auswirkungen des Sonderprogramms WeGebAU, in dessen Rahmen die Bundesagentur für Arbeit (BA) Weiterbildungsmaßnahmen für Beschäftigte über 45 Jahren subventioniert. Wir wenden dynamische Matchingmethoden nach Crépon et al. (2009) an und nutzen neue Informationen aus den Prozessdaten der BA. Wir konzentrieren uns auf die Verbleibswahrscheinlichkeit in Beschäftigung und schätzen getrennte Effekte nach Geschlecht, Alter, Berufsstellung und geplanter Programmdauer. Es zeigt sich, dass WeGebAU die Wahrscheinlichkeit zwei Jahre nach Programmstart noch abhängig beschäftigt zu sein, um ein bis 2,5 Prozentpunkte erhöht. Der Effekt ist stärker für Teilzeitbeschäftigte und Teilnehmer an längeren Weiterbildungsmaßnahmen. Unsere Analysen weisen darauf hin, dass die Effekte in erster Linie auf einen verzögerten Arbeitsmarktrückzug zurückzuführen sind, und dass die Teilnahme auf Ebene der Betriebe selektiv ist.
Keywords: J18; J14; I21; 330; Further training for employees; government-funded programs; dynamic matching